McCall's essential guide to sewing - Binder, Brigitte (Sixth&Spring Books, 2014)
"Whether you're a total novice or practically a pro, this indispensable guide from McCall's is packed with instructions, tips, and fascinating facts that every sewer needs. From mastering the most basic techniques to the ins and outs of using a sewing machine, from mending tears to altering, embellishing, and finishing, this beautifully presented and richly illustrated book has the lowdown"--